C aka y = -4.6 and y = 4.6
Step-by-step explanation:
i just took the unit review test on edg. :)
(x-2)squared +y squared=20
Answer:
16
Step-by-step explanation:
4 x 10 = 40
6 x 4 = 24
40 - 24 = 16
It is number 3 why beacseu if u don’t have the length them u can’t do the equation
The explicit formula is a(n) = 15(n – 10)
<u>Solution:</u>
Given, a term a(19) = 135 and common difference d = 15
We have to find the explicit formula.
Now, we know that, a(n) = a + (n – 1)d where a(n) is nth term, a is first term, d is common difference,
So, for a(19)
![\begin{array}{l}{\rightarrow a(19)=a+(19-1) 15} \\\\ {\rightarrow 135=a+18 \times 15} \\\\ {\rightarrow a=135-270} \\\\ {\rightarrow a=-135}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%5Crightarrow%20a%2819%29%3Da%2B%2819-1%29%2015%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%20135%3Da%2B18%20%5Ctimes%2015%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%20a%3D135-270%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%20a%3D-135%7D%5Cend%7Barray%7D)
Now, we know that, an explicit formula is an expression for finding the nth term,
So, in our problem, expression for finding nth term is a + (n – 1)d
![\begin{array}{l}{\rightarrow-135+(n-1) 15} \\\\ {\rightarrow-135+15 n-15} \\\\ {\rightarrow 15 n-150} \\\\ {\rightarrow 15(n-10)}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%5Crightarrow-135%2B%28n-1%29%2015%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow-135%2B15%20n-15%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%2015%20n-150%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%2015%28n-10%29%7D%5Cend%7Barray%7D)
Hence, the explicit formula is a(n) = 15(n – 10).